O czasie wolnym słuchaczy Uniwersytetu III Wieku w Cieszynie - Olimpia Gogolin; Eugeniusz Szymik (Edukacja Ustawiczna Dorosłych)
This article aims at examining the issue of free time spent by participants of activities conducted at the University of the Third Age in Cieszyn. In the theoretical part, we present definitions, functions and forms of spending free time and we describe the University of the Third Age in Cieszyn. In the practical part, we present the results of a survey based on a questionnaire carried out in 2018.